2013
DOI: 10.1007/s00132-012-2032-6
|View full text |Cite
|
Sign up to set email alerts
|

Verwendung von Allergieimplantaten in Deutschland

Abstract: In a representative survey among members of the working group for joint replacement (AE) in Germany (86.7% response) it was found that 0.6% of patients with total knee arthroplasty (TKA) and 1.2% of patients with total hip arthroplasty (THA) may have a problem due to hypersensitivity to nickel or cobalt after implantation. Only one third of them may need revision surgery. Although patients with hypersensitivity are rare 84% of surgeons would prefer to use a specially coated allergy implant for knee arthroplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…In addition, the opinions among surgeons remain divided. 80% of surgeon would use so‐called nickel‐free implants if they knew patients were allergic to Nickel according to a previous survey [40]. In contrast, a Delphi consensus study concluded that surgeons use standard implants for self‐reported nickel allergic patients and that there is no role for pre‐operative metal sensitivity screening [39].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the opinions among surgeons remain divided. 80% of surgeon would use so‐called nickel‐free implants if they knew patients were allergic to Nickel according to a previous survey [40]. In contrast, a Delphi consensus study concluded that surgeons use standard implants for self‐reported nickel allergic patients and that there is no role for pre‐operative metal sensitivity screening [39].…”
Section: Discussionmentioning
confidence: 99%
“…Zwischenzeitlich ist die Metallendoprothetik über einen medical device alert durch die britische Gesundheitsbehörde unter Beobachtung gestellt und es wurde in der FDA safety communication metal‐on‐metal hip implants von 2013 bei Metallallergie von der Entscheidung für eine Versorgung mit MoM‐Modellen abgeraten. Bei einer deutschlandweiten Befragung von aktiven Mitgliedern der Arbeitsgemeinschaft Endoprothetik wurden zu 122 159 im Jahr 2009 durchgeführten Endoprothesenoperationen Angaben zum Themenbereich „Allergie“ gemacht . Auch wenn dies nur einem Teil der Gesamtendoprothetik des Jahres entspricht, so lassen sich daraus doch weitere Schlüsse ziehen: Von 1 530 Patienten mit bekannter Nickel‐ oder Cobaltallergie wurden 1 285 (84 %) bereits primär präventiv mit einer alternativen Endoprothesenvariante für Patienten mit Metallallergie versorgt: Dazu zählen Endoprothesen aus Alternativmaterialien wie z.…”
Section: Einführungunclassified
“…The 2013 FDA safety communication metal‐ on‐metal hip implants advised against the use of MoM models in patients with metal allergy. In a nationwide survey of active members of the Working Group Joint Implants (Arbeitsgemeinschaft Endoprothetik), information on the topic “allergy” was provided for 122,159 replacement arthroplasties performed in 2009 . Even tough this number only corresponds to a percentage of the total number of joint replacements performed that year, it allows for some conclusions: of 1,530 patients with known nickel or cobalt allergy, 1,285 (84 %) were already preemptively treated with an alternative implant suited for patients with metal allergy.…”
Section: Introductionmentioning
confidence: 99%